Adapting New Technologies of Exposure and Promotion for Agro-Tourism Enterprises with Comparative Evaluations - Dimitriadou , Eleni; Lamprouli , Ioanna; Iakovidou, Olga (Asian Journal of Agriculture and Rural Development, 2019)
As we are well aware that today the positive use of internet and shared websites comprise of various strong and prolific tools for business for the promotion of their products and services through world-wide advertisement, especially for small businesses in the rural areas. The paper at hand comprises of initial comparative study of the websites of the agro-tourism enterprises, which are located in Central Macedonia in Greece, with the very specific aim of investigating their adaptability plan and criteria towards the new technologies of exposure and promotion, since Central Macedonia is a larger and more developed region. Initially in 2010, 158 websites of agro-tourism enterprises were assessed, which were again surveyed in 2018. Through a census process, the data collecting method was adopted in this research, whereas the websites’ assessment was conducted with the assistance of five criteria process, viz. content, interactivity, site attractiveness, promotional value and security, which were selected through literature review on the relevant subject. The evaluation confirmed our assumptions that the adaptability of new technologies for the agro-tourism enterprises in Central Macedonia, Greece had improved, but the results of all evaluation criteria tend to show very low improvement, as seen in this century.